The Effect of Spraying Boron and Seaweed Extracts (kelpak) on Vegetative Growth Characteristics and Concentration of Some Medically Active Substances for Lemon Grass (Cymbopogon Citratus L.) - Nazar Hasan, Mohammed; ., . (International Journal of Engineering and Technology, 2018)
This study includes the effect of spraying boron and seaweed extracts kelpak in the vegetative growth characteristics and concentration of some medically active substances for lemongrass plant. The experiment used a randomized complete block design with three replications. The Medians treatments have compared using Duncanâ€™s test with multi limits at 5% possibility. The results arrived at can be summed up as follows. Discriminate treatment (B1K1) the highest rate of number of leaves (9.61 leave/plant) and the highest rate in plant height (134.14 cm), compared with comparison transaction ( B0K0 ) it gave the lowest rate for the number ofÂ leavesÂ andÂ lessÂ heightÂ ofÂ the plants. While theÂ treatmentÂ givingÂ overlap (B2K2) theÂ highestÂ moral valueÂ PercentageÂ ofÂ dry matter for total vegetativeÂ (24.00)Â and theÂ highestÂ rateÂ ofÂ percentage of dry matter for total root (33.00) andÂ theÂ highestÂ rateÂ ofÂ leaves areaÂ (168.08 cm2/leave) and theÂ highestÂ total chlorophyll concentration (35.18 SPAD) Compared with theÂ least in comparison transaction ( B0K0 ) thatÂ gave less rate in percentage of dry matter for total vegetative and root and theÂ less total chlorophyll concentration. Influenced treatment (B1K1) in the concentrations of the activeA substances to give it the highest concentrations ofÂ Myrcene (3.47 mg/gm) and Citral (28.01 mg/gm) and Limonene (42.72 mg/gm) and Geraniol (38.42 mg/gm) comparedÂ to theÂ rest of theÂ other transactions, while the lower concentrations of these in the treatment comparison ( B0K0).Â Â